'The lived experience of climate change': creating open educational resources and virtual mobility for an innovative, integrative and competence-based track at Masters level. (1st January 2011) - Wilson, Gordon; Abbott, Dina; de Kraker, Joop; Salgado Pérez, Paquita; van Scheltinga, Catharien Terwisscha; Willems, Patrick
This paper explores a new integrative approach to climate change education at Masters level. Drawing on the authors' involvement in a European Union Erasmus project, it is argued that the diversity of knowledge(s) on climate change are a source of active/social learning. The wide variety of disciplinary, sectoral and lived experiential (both individual and collective) knowledge(s) are all considered legitimate in this exercise, the aim of which is to construct new interdisciplinary knowledge from their boundary interfaces. We further argue for a corresponding pedagogy based on developing transboundary competences – the ability to engage in social learning and action through communicative engagement across knowledge boundaries. We acknowledge that the challenges for enacting transboundary competence are considerable when it requires mobility across epistemological, even ontological, boundaries. The challenges are further compounded when the communicative engagement across space and time requires virtual mobility which is ICT-enabled. Nevertheless, meeting them is a normative goal, not only for this expanded, integrative approach to climate change education, but also for a global resolution of climate change itself.